Fabrication of Iron Aluminide Coatings (Fe3Al and FeAl3) on Steel Substrate by Self-Propagating High Temperature Synthesis (SHS) Process - Mohammadkhani, S.; Bondar, N.; Vahdati-Khaki, J.; Haddad-Sabzevar, M. (Journal of Coating Science and Technology, 2017)
Iron aluminides (Fe3Al and FeAl3) coatings were fabricated on a steel substrate by self-propagating high temperature synthesis (SHS) method. Raw materials, Fe and Al powders, were mixed at two different stoichiometry ratios (3:1 and 1:3). The mixtures and the substrate were placed in a furnace at 950 Â°C to ignite the SHS process. Coating phases were investigated using X-ray diffraction (XRD) and Energy Dispersive Spectroscopy (EDS). The microstructure of the coatings was analyzed with optical microscopy (OM) and scanning electron microscopy (SEM). The results confirmed that it is possible to produce Fe3Al and FeAl3 coatings on steel substrate using SHS method. In addition, the results show that the coatings were composed of two different phases and their microstructures were non-porous and dense. Wear resistance of the coatings were higher than that of the substrate.